The effect of torch distance on weldability of dissimilar welding - Ashaari, Ibrahim (2013)
This project presents the effect of parameter in welding process on the weldability of dissimilar welding. The parameters that have been focusing are torch distance or also known as arc length. Studies were made to investigate the effect of torch distance on weldability of dissimilar welding and also to find the optimize parameters for welding dissimilar metal between stainless steel and carbon steel. The experimental data was analyzed by using Taguchi method and also Analysis of Variance. The output of this research is the visual inspection, microstructure analysis, hardness test and also tensile test. The optimized parameter for hardness test and tensile test is obtained by using Taguchi method. The result obtained for this studies is the effect of torch distance is significant based on the four output, however if compare to others parameter it is the least significant. The optimized parameter for hardness test is 90 A, 26 V, 4 mm, 4 mm/s, while for tensile test is 95 A, 24 V, 2 mm, and 4 mm/s.